Teaching colonial history and national identity development among palestinian students in Israel resisting colonisation through student activism - Makkawi, Ibrahim (CLACSO, 2017)
This research project explores the colonial hegemony and pedagogical contradictions imbedded within the process of collective-national identity development among Palestinian students in the Israeli formal educational system through inductive examination of the dialectical interplay between the three agents of the formal educational process; namely, the formal curriculum, the students and the teachers. The study utilised Grounded Theory (Glaser & Strauss, 1967) as a qualitative research method and used three sets of data: (a) the formal curriculum of history used in grades 7-12 in Palestinian schools in Israel, (b) in-depth qualitative interviews with 7 History Palestinian teachers who are officially employed by the Israeli government and teach Palestinian students in the segregated Palestinian schools in Israel, (c) in-depth interviews with 14 Palestinian college students who are graduates of this formal educational system.